The Geneva University Global Health and Human Rights Summer School: A 5-Year Intercultural Collaborative Experience - Chastonay, Philippe; Mpinga, Emmanuel K. (Frontiers in Public Health, 2018)
Education and training in human rights has been set as a priority by the United Nations. Health and human rights are closely related. Training professionals from various backgrounds in human rights might ultimately contribute to improve the health of individuals and communities. We present the 5 years’ experience with a 3-week residential Global Health and Human Rights Course developed at the University of Geneva and implemented with the support/participation of international organizations (IOs) and non-governmental organizations active in the health and human rights sector. Over the years, roughly 150 students from 43 nationalities, with many different educational backgrounds, attended the course. The male/female ratio was 1/5. The adopted educational approach was multifold and comprised lectures from academics and experts with field experience, group work, individual case studies, journal clubs, and site visits. Evaluation data show that site visits at IOs were highly appreciated as well as networking opportunities among students, with academics and experts with field experience. The variety of topics discussed was, at times, “too much”; yet, it allowed students to measure the extent of the challenges the field is facing. The adopted active learning approach facilitated the exchange of experiences among students and allowed them to get acquainted with different cultural sensitivities. The Global Health and Human Rights Summer-School of the University of Geneva allowed its participants, coming from all over the world, to identify challenges of the interlinked fields of health and human rights, reflect upon their underlying causes, and imagine possible solutions. Sharing our experience will hopefully help passionate educators around the world to develop similar programs.